An analysis of the new urbanization’s ecological driving factor on the environment: based on the LMDI method - Ching, Feng; Xiao-Mei Liu (Maejo International Journal of Energy and Environmental Communication, 2021)
The new urbanization policy emphasizes ecosystem friendliness. However, there is little research on new urbanization’s effect on the ecological environment. This paper builds the LMDI model to decompose the ecological environment into three aspects: green area, wastewater discharge, and industrial solid waste production, to analyze the urbanization driving effect of Fujian Province in 2011-2018. The results show that the green area will increase due to economic-driven and urbanization-driven influences. Land-use-driven will cut down Wastewater discharge and waste generation. Among them, the economic-driven and land-use-driven have opposite effects.